Clinical case of neonatal acute lymphoblastic leukemia - N.S. Artiomova (Zdorovʹe Rebenka, 2019)
The article presents a clinical case of neonatal acute lymphoblastic leukemia in a child aged 22 days, with damage to the central nervous system and testicular involvement in the pathological process. The manifestation of clinical signs in the neonatal period was in the form of jaundice syndrome with early neonatal anemia, hydrocele. During the initial visit to the doctor and examination for neonatal jaundice, leukocytosis was found, as well as blastosis with the presence of intermediate forms of neutrophils, anemia (Hb 108 g/l). According to the myelogram, bone marrow hypocellularity was revealed, blasts — 79.6 %, cytochemical study of blast cells detected FAB-L1 type with pro-B-ALL-type immunophenotype. The molecular genetic study of the bone marrow revealed AF4/MLL t (4; 11) (q21; q23) translocation. According to cerebrospinal fluid study, blast cells (48 × 106/l) were detected, indicating the involvement of the central nervous system (CNS) in the pathological process. After making a diagnosis: congenital acute lymphoblastic leukemia, FAB L1 variant, pro-B-ALL type, testicular lesion, CNS involvement, positive І acute period, treatment was initiated according to the INTERFANT-06 protocol for congenital leukemia. Based on the recommendations of this protocol, taking into account the age of the child < 6 months, the dosage of polychemotherapy was corrected and 2/3 of the general therapeutic dose was prescribed along with accompanying therapy on a full scale. This patient during virtually the whole period of treatment did not show any hematologic improvement and died at the age of 48 days due to predominance of malignant process. The described clinical case confirms the need for early adequate diagnosis, which helps avoid a number of diagnostic and therapeutic errors, as well as increases the likelihood of successful treatment for this pathology.